Third Five Year Plan Progress Report 1963-64 Government of Rajasthan - Planning Commission (Planning Commission, 1963)
The year 1963-64, third year of the Plan, marked a further intensification of development effort in the State’s economy. In order to accelerate the tempo of development, with our eyes set on the national objective of achieving a self-sustained and self-generating economy, an amount of Rs. 38.35 crore was provided for the various development schemes during the current year. However considerable strain was cast on the resources of the State due to the national emergency prevailing in the country and the physical targets fixed earlier under various sectors had to be readjusted. But the State continued its all out efforts to step up production in various fields.
Directorate of Economics and Statistics, Government of Rajasthan
Directorate of Economics and Statistics, Government of Rajasthan